Prediction of Early Death in Patients with Early‐Stage NSCLC—Can We Select Patients without a Potential Benefit of SBRT as a Curative Treatment Approach?. Issue 7 (July 2016) - Klement, Rainer J.; Belderbos, José; Grills, Inga; Werner‐Wasik, Maria; Hope, Andrew; Giuliani, Meredith; Ye, Hong; Sonke, Jan‐Jakob; Peulen, Heike; Guckenberger, Matthias
ABSTRACT : Introduction: : Stereotactic body radiotherapy (SBRT) is the guideline‐recommended treatment for medically inoperable patients with peripheral stage I non–small cell lung cancer (NSCLC). This study analyzed whether short‐term (<6 months) death can be predicted reliably to select a subgroup of patients who will not have a benefit from SBRT. Methods: : A total of 779 patients with early‐stage NSCLC who had been treated with cone beam computed tomography–guided SBRT in five institutes and for whom information on overall survival during the first 6 months after treatment was available were included in this analysis. The probability of dying within 6 months after treatment was defined as the end point "early death" and modeled by multivariate logistic regression. Model fitting was performed using the least absolute shrinkage and selection operator method, and model test performance was estimated using double 10‐fold cross validation. The variables age, sex, Eastern Cooperative Oncology Group performance status, operability, forced expiratory volume in 1 second, and Charlson comorbidity index were considered for model building. Results: : Eastern Cooperative Oncology Group performance status and (to a lesser extent) operability were the most important predictors of early death, whereas the Charlson comorbidity index was associated only with the overall survival time. On the basis of the best expected test performance (area under the curve = 0.699), the risk for early death would be 8.8% (range 8.2%–13.7%) and 4.1% (3.0%–4.3%) for the 10% of patients with the highest and lowest risk, respectively. Overall, predictive performance was too low for clinical application. Conclusions: : SBRT should be offered to all patients irrespective of their comorbidities, unless the performance status of the patients and the comorbidities prevent accurate SBRT planning and delivery.